Medical-Surgical Nursing Scientific Method in Improving Clinical Competence - Ismonah Ismonah; Oktia Woro Kasmini Handayani; Wahyono Wahyono; Tri Suminar (International Conference on Science, Education, and Technology, 2023)
Problems that arise in the implementation of medical-surgical nursing clinical learning make students weak in achieving clinical competence, critical thinking skills, case analysis, and clinical decision-making. The scientific method is a learning approach that uses steps and scientific rules to implement the learning process. So that students always find out from various sources and information through observing, asking, trying, processing, presenting, concluding, and creating. This method is a learning method that touches on three domains: knowledge (cognitive), attitude (affective), and skills (psychomotor). This study aimed to assess the effectiveness of the scientific method in improving clinical competence and learning outcomes for nursing students in medical-surgical nursing courses. This study used a quasi-experimental method with the subject of nursing professional education students. The data analysis technique uses the t-test with the help of the SPSS program. The results of clinical studies before and after applying the scientific method showed differences in the pre-and post-test scores, with a p-value of 0.000. The results of this study indicate that the scientific method can improve students' clinical competence, including the ability to think critically and analyze cases.